Biodegradability Analysis of Banana Stem Fiber and Polypropylene Polymer Composites as a Substitute for Syrofoam: Analisis Uji Biodegrabilitas Komposit Serat Batang Pisang Dan Polimer Polypropylene Sebagai Pengganti Syrofoam (Jurnal Kimia dan Rekayasa, 2026)
The use of conventional plastics such as styrofoam for food packaging poses environmental issues due to their low degradability. This study aims to develop an eco friendly composite by utilizing banana stem fibers as reinforcement and recycled polypropylene as the matrix, with the addition of PLA resin, as well as to evaluate its biodegradability and mechanical properties. The composite samples were prepared using the hand lay-up method with variations in fiber length (2 cm and 6 cm) and fiber to polymer ratios (5:95, 30:70, 75:15, and 90:10). The tests conducted included biodegradability testing, tensile testing, and morphological observation using SEM. The results showed that the composite with a 6 cm fiber length and a 5:95 composition exhibited the best performance, with a tensile strength of 13.58 MPa, an elastic modulus of 20.59 MPa, and the highest biodegradation rate of 25.75% within 10 days. SEM analysis revealed weaknesses in interfacial bonding, such as voids and fiber pull-out, indicating the need for further optimization, such as the use of a coupling agent. Overall, this composite demonstrates potential as an environmentally friendly alternative to styrofoam for light to medium applications.  AbstrakPenggunaan plastik konvensional seperti styrofoam sebagai kemasan makanan menimbulkan permasalahan lingkungan karena sifatnya yang susah terdegradasi. Penelitian mempunyai tujuan untuk mengembangkan komposit ramah lingkungan dengan menggunakan serat batang pisang sebagai bahan penguat dan polypropylene daur ulang sebagai matriks, dengan tambahan resin PLA, serta mengetahui sifat biodegrabilitas dan mekaniknya. Sampel komposit dibuat dengan metode hand lay-up menggunakan variasi panjang serat (2 cm dan 6 cm) serta komposisi serat:polimer (5:95, 30:70, 75:15, dan 90:10). Pengujian meliputi uji biodegrabilitas, uji tarik, dan pengamatan morfologi dengan SEM. Hasil menunjukkan bahwa komposit dengan panjang serat 6 cm dan komposisi 5:95 memiliki performa terbaik, dengan kekuatan tarik 13,58 MPa, modulus elastisitas 20,59 MPa, dan tingkat biodegradasi tertinggi sebesar 25,75% dalam 10 hari. Uji SEM menunjukkan masih terdapat kelemahan pada ikatan antar fasa berupa void dan fiber pull-out, yang menunjukkan perlunya optimasi lebih lanjut, seperti penggunaan agen kopling. Secara keseluruhan, komposit ini memiliki potensi sebagai alternatif pengganti styrofoam untuk aplikasi ringan hingga menengah yang lebih ramah lingkungan.